2016
DOI: 10.1371/journal.pone.0155986
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Enhances NPP, N Retention, and Soil Microbial Diversity in Experimental Urban Grassland Assemblages

Abstract: Urban grasslands, landscapes dominated by turfgrasses for aesthetic or recreational groundcovers, are rapidly expanding in the United States and globally. These managed ecosystems are often less diverse than the natural or agricultural lands they replace, leading to potential losses in ecosystem functioning. Research in non-urban systems has provided evidence for increases in multiple ecosystem functions associated with greater plant diversity. To test if biodiversity-ecosystem function findings are applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…In a case study in Berlin, Germany, Maurer et al (2000) found 275 different wild vascular plant species growing in park meadows and lawns, with some species being endangered or threatened with extinction (according to regional Red Lists). Recent research has also found higher levels of ecosystem functioning in more diverse urban grassland communities, such as reduced nitrate leaching (Thompson & Kao-Kniffin 2016). In addition to the ecological perspective, attractiveness and psychological benefits for the city population were proven to be higher for species-rich compared to species-poor sites (Fuller et al 2007;Lindemann-Matthies et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a case study in Berlin, Germany, Maurer et al (2000) found 275 different wild vascular plant species growing in park meadows and lawns, with some species being endangered or threatened with extinction (according to regional Red Lists). Recent research has also found higher levels of ecosystem functioning in more diverse urban grassland communities, such as reduced nitrate leaching (Thompson & Kao-Kniffin 2016). In addition to the ecological perspective, attractiveness and psychological benefits for the city population were proven to be higher for species-rich compared to species-poor sites (Fuller et al 2007;Lindemann-Matthies et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While it is only one study, the results do parallel findings of a decade-long study in perennial grassland biodiversity-ecosystem function (BEF) research that suggests increasing plant species diversity will enhance root biomass, soil carbon, and N retention (Pasari et al, 2013). Linkages between above and belowground diversity were determined by Thompson and Kao-Kniffin (2016) using terminal restriction fragment length polymorphism (T-RFLP) community fingerprinting techniques. When Zhalnina et al (2015) used next-generation sequencing techniques, which generates more detailed taxonomic data than community fingerprinting, they found that plant species richness and plant productivity were not significantly related to microbial diversity.…”
Section: Plant Species Compositionmentioning
confidence: 70%
“…Increased SOM if turf species are deeper rooting (Qian et al, 2010); specific turfgrass species differences in soil C, N, and SOM accumulation (Law et al, 2017); increased soil N retention and turf productivity with diverse turf systems (Thompson and Kao-Kniffin, 2016); the soil microbiome across different urban grasslands in the Mid-Atlantic region pre-and post-construction were more similar than different, but were enriched with copiotrophic bacteria (Crouch et al, 2017) Soil disturbances/cultivation May stimulate SOM mineralization due to soil aeration and degradation of soil aggregates, but SOM effects may be offset by improved plant growth (Murphy and Ebdon, 2013); soil disturbance does not appear to significantly alter the soil microbiome once adapted to typical lawn edaphic and management conditions (Yao et al, 2006;Bartlett et al, 2007;Shi et al, 2012;Crouch et al, 2017) These potential effects may vary by the intensity of each management practice, geographically, and under different management goals. This review and this table present preliminary attempts to link multiple management practices to different soil nutrient cycles via impacts on the soil microbiome.…”
Section: Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Turfgrass landscapes have expanded rapidly in recent decades and are the predominant vegetation cover in urbanizing ecosystems in the USA . The total turfgrass area, including all residential areas, commercial areas, athletic fields, golf courses, institutional lawns, and parks, in the USA is 163 812 km 2 (±35 850 km 2 for upper and lower 95% confidence interval bounds) .…”
Section: Introductionmentioning
confidence: 99%